2014
DOI: 10.1111/jvp.12143
|View full text |Cite
|
Sign up to set email alerts
|

A physiologically based pharmacokinetic model for quinoxaline‐2‐carboxylic acid in rats, extrapolation to pigs

Abstract: A multi-compartment physiologically based pharmacokinetic (PBPK) model to describe the disposition of cyadox (CYX) and its metabolite quinoxaline-2-carboxylic acid (QCA) after a single oral administration was developed in rats (200 mg/kg b.w. of CYX). Considering interspecies differences in physiology and physiochemistry, the model efficiency was validated by pharmacokinetic data set in swine. The model included six compartments that were blood, muscle, liver, kidney, adipose, and a combined compartment for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…A PBPK model was recently published for CYA's other metabolite, QCA, in rats and pigs (Yang et al, 2015). In contrast to the present work, it was limited to the description of the kinetics of the metabolite, but not the parent compound.…”
Section: Parameter Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations
“…A PBPK model was recently published for CYA's other metabolite, QCA, in rats and pigs (Yang et al, 2015). In contrast to the present work, it was limited to the description of the kinetics of the metabolite, but not the parent compound.…”
Section: Parameter Sensitivitymentioning
confidence: 99%
“…Moreover, in the previous model, liver was considered to be the sole site of biotransformation (Yang et al, 2015). Since it had been demonstrated that CYA could be metabolized by intestinal microsomes and microbial flora, and radiotracer was observed both in feces and bile as well as urine (Xu et al, 2012), the present model incorporated A c c e p t e d M a n u s c r i p t these dynamic processes to more comprehensively describe the depletion of CYA and BDCYA in pigs.…”
Section: Parameter Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, PBPK modeling has been widely used in the area of veterinary medicine, from the prediction of drug tissue residues (Huang et al, ; Leavens et al, ; Yang et al, ), estimating the withdrawal time (Buur, Baynes, Smith, & Riviere, ; Yang, Huang, et al, ; Yang, Zhou, et al, ), to facilitating the food safety assessment (Henri, Carrez, Meda, Laurentie, & Sanders, ; Lin, Gehring, Mochel, Lavé, & Riviere, ; Yang, Huang, et al, ; Yang, Zhou, et al, ). In this study, a PBPK model was established for heavy sows based on a previous generic PBPK model for swine and cattle (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%